The comparison of Body Mass Index (BMI) and Muscle Mass Index (MMI) as a mortality predictor in patients with malignant jaundice at Dr. Sardjito General Hospital, Yogyakarta, Indonesia - Briand Iggreinus Pollah; Adeodatus Yuda Handaya; Agus Barmawi (Intisari Sains Medis, 2021)
Background: Jaundice is found to be a clinical manifestation of malignancy. Around 70% of all jaundice cases are caused by malignancy. Another complication of malignancy is decreasing the Muscle Mass Index (MMI), also called sarcopenia. MMI in malignant jaundice increases the mortality rate. Body Mass Index (BMI) is describing the nutritional status of a person. Due to malnutrition, morbidity and mortality increase. This study aims to compare the MMI and BMI in patients with malignant jaundice to predict the outcome of mortalityMethods: This study is a retrospective cross sectional non-experimental epidemiologic analysis. Samples were taken from medical reports at Sardjito Hospital from April 2019 - March 2020. A CT scan calculated MMI at the third lumbar vertebrae. BMI was evaluated by body weight (kg) divided by height (m) square (kg/m2). Data were analyzed using SPSS version 20 for Windows.Results: Most of respondents were males (55.0%), following by age > 50 (62.5%), stage 3 (62.5%), ASA 2 (92.5%), albumin < 3.5 g/dL (82.5%), CA19-9 > 37 U/ml (57.5%), CEA < 5 ng/ml (62.5%), and total bilirubin > 1.5 mg/dL (90.0%), normal BMI (62.5%), survive (77.5%), and low MMI (72.5%). There was no significant relationship between MMI (OR: 5.71; 95%CI: 0.60-134.12) and BMI (OR: 0.15; 95%CI: 0.02-1.34) to the mortality risk (p>0.05).Conclusion: MMI had a higher incidence of mortality compared to BMI in malignant jaundice. However, there was no significant relationship between MMI and BMI to predict mortality.